Peningkatan Mutu Madrasah Tsanawiyah di Kota Jambi - Rahman, K.A. (Nadwa, 2012)
This research is aimed to analyze the meaning or the role of the headmaster leadership contribution, the organization climate and the society participation for the quality of Madrasah, and to find the strategy of Madrasah quality devel-opment. Trough survey with quantitative approach and questioner technique, itâs found that the headmaster has a significant contribution toward madrasah quali-ty. The headmaster has not communicated the school programs to society. The organization climate gives a significant contribution too toward the madrasah. There is no optimal interaction between the teachers and the headmaster. The society participation has a significant contribution toward the school quality. Research finding appoints that madrasah hasnât completely involved society yet. The quality of madrasah increases by motivating the students to often participate in the competitions, training communication skill, and by encouraging them to achieve some achievements that can increase their confidence.